2011
DOI: 10.1055/s-0030-1256872
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of IgG4 in bile: a new approach for the diagnosis of IgG4-associated cholangiopathy

Abstract: The study demonstrates that bile IgG4 measurement is possible and may help to distinguish IAC from other diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 7 publications
(17 reference statements)
1
22
0
Order By: Relevance
“…In contrast, ANCA was frequently found in the serum of patients without PSC. This finding corroborates a previous study in which we were able to distinguish IgG 4associated cholangitis from other biliary diseases by measuring IgG 4 in the bile with a higher sensitivity and specificity than IgG 4 in the serum [14]. Consequently, the analysis of IgG ANCA in bile may be helpful to distinguish PSC from other biliary disorders.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, ANCA was frequently found in the serum of patients without PSC. This finding corroborates a previous study in which we were able to distinguish IgG 4associated cholangitis from other biliary diseases by measuring IgG 4 in the bile with a higher sensitivity and specificity than IgG 4 in the serum [14]. Consequently, the analysis of IgG ANCA in bile may be helpful to distinguish PSC from other biliary disorders.…”
Section: Discussionsupporting
confidence: 91%
“…The analysis of the markers in bile may be more sensitive than of those in serum, which is pathophysiologically plausible since the cause of biliary diseases typically resides in the epithelium, where various markers are secreted [25]. We recently demonstrated that bile measurements are helpful in the diagnosis of biliary diseases [12][13][14]. Because the inflammation of PSC takes place at the biliary epithelium, we hypothesized that a local immune response might occur in the presence of ANCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a recent study from Europe, elevated IgG4 was seen in 6/23 (26.1%) of PSC patients similar to our study. 26 In our cohort of 142 patients, only 50 had serum IgG4 measured. To account for the possible bias involved in serum IgG4 measurement, we had compared disease activity in the 50 patients with serum IgG4 measurement and the remaining 92 patients who did not have IgG4 measured.…”
Section: Figurementioning
confidence: 78%
“…Biopsies of the duodenal papilla are easily accessible [72], yet only moderately sensitive, and precaution must be taken to avoid papilla injury with an increased risk of complicating pancreatitis. IgG4 is also detectable in bile [73]. Differential diagnostic assessments versus malignancy (e.g., cholangiocarcinoma) may sometimes represent a challenge [74].…”
Section: Igg4 and Sclerosing Cholangitismentioning
confidence: 99%